The politics of ebooks. (1st September 2017) - Sang, Yoonmo
Ebooks have emerged as one of the popular means of reading, but little is known about how ebook usage by the general public and the ability of public lending libraries to serve their patrons are being constrained by various sociocultural factors such as restrictive licensing agreements that publishers demand. This study identifies the various constraints through the lens of Lessig's four modalities to better understand how the ecosystem of ebooks that includes legal and economic conditions is affected by the modalities. In doing so, this study examines the shift towards the licensing of ebooks and the proprietary schemes of digital rights management with a particular focus on the diminishing capability of public lending libraries to advance the public interest in a democratic society. In the age of licensing, the mission of public libraries as 'equalizing institutions' should be upheld to the fullest.